Arsenic removal from aqueous solutions by adsorption on red mud - Altundoğan, Hamdi Soner; Altundoğan, Sema; Tümen, Fikret; Bildik, Memnune (My University, 2000)
Use of red mud, which is a waste product from bauxite processing, has been explored as an alternate adsorbent for arsenic in this study. The tests showed that the alkaline aqueous medium (pH 9.5) favored the removal of As(III), whereas the pH range from 1.1 to 3.2 was effective for As(V) removal. The process of arsenic adsorption follows a first-order rate expression and obeys the Langmuir's model. It was found that the adsorption of As(III) was exothermic, whereas As(V) adsorption was endothermic. It would be advantageous to use this residue as an adsorbent replacing polyvalent metal salts.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Arsenic adsorption; Red mud; Langmuir isotherm